Board Interlocking and Accounting Choices in Brazilian Electric Energy Companies with Stock Exchange - Flávio Ribeiro; Ademir Clemente (BBR: Brazilian Business Review)
This article aims to analyze the influence of stability and the intensity of board interlocking on accounting choices. The sample consists of 57 companies in the electricity sector out of a total of 59 with shares traded on Brasil, Bolsa, Balcão (B3), analyzed in a a period ranging from 2010 to 2016. This resulted in 177 different connections between companies. Company stability and intensity of existing relationships between the boards were used as proxies for an interlocking framework. For determining the accounting choice, an attempt was made to identify similarities between the choices adopted by the companies. The findings reveal considerable changes in the connection structures of companies. This began with the formation of a major network in the years 2010 and 2011, and ended with five well-defined groups in 2016. The results suggest that stability and intensity of connections favor dissemination of accounting choices. This is especially true for choices related to measurement and classification. These findings converge with Connelly and Slyke (2012) according to whom the existence of common counselors favor the access and dissemination of information between companies.